The Utilization of Seaweed Eucheuma cottonii in the Production of Antiseptic Soap - Ace Baehaki; Shanti Dwita Lestari; Dica Fusva Hildianti (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
The aim of study was to formulate solid soap made from Eucheuma cottonii seaweed which has antiseptic properties. This study used a Complate Randomized Design (CRD) with one factor adding extractE. cottonii seaweed (0 ppm, 250 ppm, 500 ppm and 750 ppm). The steps included sample preparation, extraction, production of antiseptic soap, chemical physics test (moisture content, pH, free alkali, foam stability, and hardness) and antibacterial test. The results showed that the addition of E. cottonii seaweed extract had a significant effect on free alkali, foam stability, and soap hardness except the moisture contentand acidity (pH) of the soap. Moisture content of solid soap ranged 20.03-27.62%, pH 11.22-11.57, the free alkali value was 0.05-0.53%, foam stability was 42.77-74.42%, and hardness was in the range of 102.10-387.84%. Antibacterial activity test showed inhibitory diameter in E. cottonii extract soap ranged 11.08-17.15 mm, classified as a strong antibacterial activity (> 11 mm), while the antibacterial inhibitory diameter of E. cottonii extract was 0–12.26 mm. The higher the concentration of seaweed extract E. cottonii, the higher the inhibition zone (antibacterial activity) of soap produced. The best treatment of antiseptic soap produced was seaweed extract with concentration of 750 ppm which had the highest inhibition zone against S. aureus compared to other treatments.